FTY720 reduces post-sschemic brain lymphocyte influx but does not improve outcome in permanent murine cerebral ischemia - Liesz, Arthur; Sun, Li; Zhou, Wei; Schwarting, Sönke; Mracskó, Eva; Zorn, Markus; Bauer, Henrike; Sommer, Clemens; Veltkamp, Roland (PLOS ONE, 2011)
Background The contribution of neuroinflammation and specifically brain lymphocyte invasion is increasingly recognised as a substantial pathophysiological mechanism after stroke. FTY720 is a potent treatment for primary neuroinflammatory diseases by inhibiting lymphocyte circulation and brain immigration. Previous studies using transient focal ischemia models showed a protective effect of FTY720 but did only partially characterize the involved pathways. We tested the neuroprotective properties of FTY720 in permanent and transient cortical ischemia and analyzed the underlying neuroimmunological mechanisms. Methodology/Principal Findings FTY720 treatment resulted in substantial reduction of circulating lymphocytes while blood monocyte counts were significantly increased. The number of histologically and flow cytometrically analyzed brain invading T- and B lymphocytes was significantly reduced in FTY720 treated mice. However, despite testing a variety of treatment protocols, infarct volume and behavioural dysfunction were not reduced 7d after permanent occlusion of the distal middle cerebral artery (MCAO). Additionally, we did not measure a significant reduction in infarct volume at 24h after 60 min filament-induced MCAO, and did not see differences in brain edema between PBS and FTY720 treatment. Analysis of brain cytokine expression revealed complex effects of FTY720 on postischemic neuroinflammation comprising a substantial reduction of delayed proinflammatory cytokine expression at 3d but an early increase of IL-1β and IFN-γ at 24 h after MCAO. Also, serum cytokine levels of IL-6 and TNF-α were increased in FTY720 treated animals compared to controls. Conclusions/Significance In the present study we were able to detect a reduction of lymphocyte brain invasion by FTY720 but could not achieve a significant reduction of infarct volumes and behavioural dysfunction. This lack of neuroprotection despite effective lymphopenia might be attributed to a divergent impact of FTY720 on cytokine expression and possible activation of innate immune cells after brain ischemia.